2020
DOI: 10.1080/17453674.2020.1853340
|View full text |Cite
|
Sign up to set email alerts
|

Variation and trends in reasons for knee replacement revision: a multi-registry study of revision burden

Abstract: Background and purpose — Studies describing time-related change in reasons for knee replacement revision have been limited to single regions or institutions, commonly analyze only 1st revisions, and may not reflect true caseloads or findings from other areas. We used revision procedure data from 3 arthroplasty registries to determine trends and differences in knee replacement revision diagnoses. Patients and methods — We obtained aggregated data for 78,151 revision knee replacement procedures record… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 49 publications
4
18
0
Order By: Relevance
“…We found infection, loosening, instability, and patellar reasons were the most common diagnoses for revision of TKR for OA in all 3 registries, with the only difference seen in the KPJRR where 98% of TKR had a primary patellar resurfacing and patellar causes for revision were rare. These findings, along with the timing of these revisions, are consistent with previous studies ( 25 , 28 , 29 ). When patient and prosthesis factors for revision reasons were studied, 15 of 56 possible factor/reason combinations showed between-registry consistency, varying from 3 concordant factors for each of revision for fracture and loosening, and no factor consistency for revision for pain.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…We found infection, loosening, instability, and patellar reasons were the most common diagnoses for revision of TKR for OA in all 3 registries, with the only difference seen in the KPJRR where 98% of TKR had a primary patellar resurfacing and patellar causes for revision were rare. These findings, along with the timing of these revisions, are consistent with previous studies ( 25 , 28 , 29 ). When patient and prosthesis factors for revision reasons were studied, 15 of 56 possible factor/reason combinations showed between-registry consistency, varying from 3 concordant factors for each of revision for fracture and loosening, and no factor consistency for revision for pain.…”
Section: Discussionsupporting
confidence: 93%
“…While there seems no direct link of the implant–bone interface to the bearing, cementless fixation may have been selected for more active patients ( 44 ). Surgeons may also have difficulty deciding between wear and loosening as the primary mechanism leading to revision ( 25 ). The lack of further associations with wear may be due to the relative rarity of revisions for this diagnosis, particularly in Sweden.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Following on from this, it is evident that comparatively little is understood about the epidemiology of re-revision KR (that is second or subsequent revision procedures), despite their considerable impact on individual patients and their potential to consume large amounts of health resource [18] . A recent multi-registry study from Australia, Sweden and the United States found that the proportion of rKR performed for infection had increased in recent years [19] , with one hypothesis that an increase in the rate of re-revision KR may be responsible.…”
Section: J O U R N a L P R E -P R O O Fmentioning
confidence: 99%
“…In a previous study we found inter-registry differences regarding reasons for knee replacement revision and theorized this was related to patient selection and prosthesis choice ( 30 ). This study (i) documents regional and temporal variation in primary TKA practice across 3 registries between 2003 and 2019 and (ii) uses a meta-analytic technique to determine the influence of each factor on the risk of revision.…”
mentioning
confidence: 99%